2021
DOI: 10.1101/2021.05.24.21257425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Humoral Response to the BNT162b2 Vaccine in Hemodialysis Patients

Abstract: Importance: Hemodialysis patients have an exceptionally high mortality from COVID-19 and this patient population often has a poor response to vaccinations. Randomized controlled trials for COVID-19 vaccines included few patients with kidney disease, therefore vaccine immunogenicity is uncertain in this population. Objective: Evaluate the SARS-CoV-2 antibody response in chronic hemodialysis patients following one versus two doses of BNT162b2 COVID-19 vaccination compared to health care worker controls and conv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…In the HDP population, presented in the current study, the seroconversion rates at 2 months after the second vaccine dose was similar to previous reports [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Initial studies demonstrated a substantial humoral response in the dialysis population, with seroconversion rates as high as 96%, though levels of antibody titers were significantly lower and more delayed compared to healthy controls [18][19][20][21][22][23][24][25][26]34]. Direct comparison of antibody titers at month 2 to those reported in previous studies is difficult, because different antibody assays were used with different definition of the immune response, titers assessed at different time points (mostly within a month after vaccination).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the HDP population, presented in the current study, the seroconversion rates at 2 months after the second vaccine dose was similar to previous reports [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Initial studies demonstrated a substantial humoral response in the dialysis population, with seroconversion rates as high as 96%, though levels of antibody titers were significantly lower and more delayed compared to healthy controls [18][19][20][21][22][23][24][25][26]34]. Direct comparison of antibody titers at month 2 to those reported in previous studies is difficult, because different antibody assays were used with different definition of the immune response, titers assessed at different time points (mostly within a month after vaccination).…”
Section: Discussionsupporting
confidence: 91%
“…In the HDP population, presented in the current study, the seroconversion rates at 2 months after the second vaccine dose was similar to previous reports [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Initial studies demonstrated a substantial humoral response in the dialysis population, with seroconversion rates as high as 96%, though levels of antibody titers were significantly lower and more delayed compared to healthy controls [18][19][20][21][22][23][24][25][26]34].…”
Section: Discussionsupporting
confidence: 89%
“…After the titles and abstracts were screened, the full texts were reviewed to further determine study eligibility. After the exclusion of irrelevant studies, including studies not addressing the outcome of interest and studies only based on ESKD with kidney transplant population, 32 studies, including 6 preprint articles, were included in the meta-analysis (eFigure 1 in the Supplement). The extracted data are summarized in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Six preprint articles were selected from the medRxiv server and another 5 studies from enrolled studies only reported the immunogenicity rates of patients receiving dialysis who did not complete the vaccination protocol (ie, those who received only 1 dose of the BNT162b, AZD1222, or mRNA-1273 vaccines). 7,[11][12][13]37 Other articles reported an antibody response rate after the second dose with or without reporting the response rate after the first dose. Three studies discussed immunogenicity rates after the booster shot.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…I G U R E 1 Flowchart of article identification and selection in the meta-analysisT A B L E 1 Antibody response data in dialysis patients after the first dose of mRNA vaccines(8,(12)(13)(14)(15) …”
mentioning
confidence: 99%